Has mexican growth been pro-poor? - Araar, Abdelkrim; Duclos, Jean-Yves; Audet, Mathieu; Makdissi, Paul (Facultad de Trabajo Social, Universidad Autónoma de Nuevo León, 2007)
This paper proposes techniques to test for whether growth has been propoor. We first review different definitions of pro-poorness and argue for the use of methods that can generate results that are robust over classes of pro-poor measures and ranges of poverty lines. We then provide statistical pro-cedures that rely on the use of sample data to infer whether growth has been pro-poor in a population. We apply these procedures to Mexican household surveys for the years of 1992, 1998 and 2004. We find strong statistical evidence that Mexican growth has been absolutely anti-poor between 1992 and 1998, absolutely pro-poor between 1998 and 2004 and between 1992 and 2004, and relatively pro-poor between 1992 and 2004 and between 1998 and 2004. The relative assessment of the period between 1992 and 1998 is statistically too weak to lead to a robust evaluation of that period.